2004
DOI: 10.1038/nm993
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear hormone receptor peroxisome proliferator–activated receptor-δ accelerates intestinal adenoma growth

Abstract: We treated Apc(min) mice, which are predisposed to intestinal polyposis, with a selective synthetic agonist of peroxisome proliferator-activated receptor-delta (PPAR-delta). Exposure of Apc(min) mice to the PPAR-delta ligand GW501516 resulted in a significant increase in the number and size of intestinal polyps. The most prominent effect was on polyp size; mice treated with the PPAR-delta activator had a fivefold increase in the number of polyps larger than 2 mm. Our results implicate PPAR-delta in the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
228
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(245 citation statements)
references
References 14 publications
13
228
0
1
Order By: Relevance
“…Peroxisome proliferatoractivated receptord may mediate the antiapoptotic effect through activation by prostacyclin (PGI(2)), a major prostaglandin with antiapoptotic activity (Gupta et al, 2000;Cutler et al, 2003). There is also cumulative evidence regarding the antiapoptotic effects of PPARd in keratinocyte and colon cancer cells (Michalik et al, 2001;Di-Poi et al, 2002;Shureiqi et al, 2003;Gupta et al, 2004). These findings suggest that PPARd may play a certain tumour-promoting role in intestinal tumours or CRC cells by modulating cell survival and apoptosis, which is in line with our observation that PPARd was exclusively expressed in those CRC cells that also exhibited highly malignant morphology.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Peroxisome proliferatoractivated receptord may mediate the antiapoptotic effect through activation by prostacyclin (PGI(2)), a major prostaglandin with antiapoptotic activity (Gupta et al, 2000;Cutler et al, 2003). There is also cumulative evidence regarding the antiapoptotic effects of PPARd in keratinocyte and colon cancer cells (Michalik et al, 2001;Di-Poi et al, 2002;Shureiqi et al, 2003;Gupta et al, 2004). These findings suggest that PPARd may play a certain tumour-promoting role in intestinal tumours or CRC cells by modulating cell survival and apoptosis, which is in line with our observation that PPARd was exclusively expressed in those CRC cells that also exhibited highly malignant morphology.…”
Section: Discussionsupporting
confidence: 88%
“…As mentioned in the Introduction, PPARd was found to be unnecessary for small intestinal polyp formation (Barak et al, 2002), but PPARd attenuated polyp formation in chemical and genetic models (Harman et al, 2004;Reed et al, 2004). By contrast, it has been reported that inactivation of the PPARd gene results in reduced tumorigenicity and in vivo growth of HCT116 colon cancer cells (Park et al, 2001) and that a specific PPARd agonist enhanced in vivo growth of intestinal adenoma of Apc min mice (Gupta et al, 2004). Moreover, a decrease in PPARd expression by nitric-oxide-donating aspirin isomers was found to be proportional to their tumour inhibitory effects in Apc min mice (Ouyang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four muscle strips were thus available per rat, allowing the paired examination of three concentrations of GW501516 (gift of Hoffmann-La Roche, Basel, Switzerland) along with an intra-individual control. Effects on fuel metabolism were initially studied at three concentrations at which GW501516 was expected to dose-dependently activate PPAR-δ (0.01, 0.1, and 1 μmol/l; referred to as low concentrations) [6,12]. When a pilot experiment with higher concentrations raised further mechanistic questions, an additional set of three concentrations, at which PPAR-δ activation was expected to be maximal, was also examined (3, 10 and 30 μmol/l GW501516; referred to as high concentrations).…”
Section: Pretreatment Periodmentioning
confidence: 99%
“…To close this gap in knowledge, we thoroughly explored the direct effects of GW501516, a potent and selective PPAR-δ agonist [6,12], on glucose handling by freshly isolated native specimens of rat skeletal muscle.…”
mentioning
confidence: 99%